Answer:120
Step-by-step explanation:
Answer:
V(w) = 6*w³ [cubic units]
Step-by-step explanation:
h height of the rectangular prism
L the length of the base
w the width of the base
Then the volume of the prism is area of the base times heigth therefore
V(p) = L*w*h [cubic units] (1)
Now the length of the base L = 2*w
And the height of the prism is h = 3*w
If we plugging these values in equation (1) we get olume of a prism as function of w then
V(w) = 2*w* w * 3*w
V(w) = 6*w³ [cubic units]
Answer:
(h o g)(5) = 20
Step-by-step explanation:
(h o g)(5) = h(g(5)) <em>This is two ways of writing the expression</em>
g(x) =
h(x) = 3x + 5 <em>g(x) and h(x) are your "plug-ins" for the expression</em>
g(5) =
=
= 5 <em>This is how you would solve for plugging in 5 to g(x)</em>
<em>Whatever you get for g(5) {the answer to it} is what you will be plugging into h(x); x being equal to g(5).</em>
h(5) = 3(5) + 5 = 15 + 5 = 20